2015
DOI: 10.1016/j.devcel.2014.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Nodal Signaling Range Is Regulated by Proprotein Convertase-Mediated Maturation

Abstract: Tissue patterning is established by extracellular growth factors or morphogens. Although different theoretical models explaining specific patterns have been proposed, our understanding of tissue pattern establishment in vivo remains limited. In many animal species, left-right patterning is governed by a reaction-diffusion system relying on the different diffusivity of an activator, Nodal, and an inhibitor, Lefty. In a genetic screen, we identified a zebrafish loss-of-function mutant for the proprotein converta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 36 publications
6
20
1
Order By: Relevance
“…Although we had not succeeded in verifying the cleavage of Hau-BMP5-8 in the germinal band, we nevertheless demonstrated that such cleavage is irrelevant to Hau-BMP5-8's ability to induce the P fate. This finding is in stark contrast to the situation in vertebrate embryos, in which overexpression of BMP4 or BMP7 with mutated cleavage sites has a dominant-negative effect (Hawley, et al 1995); on the other hand the apparent irrelevance of convertase-mediated cleavage in the leech germinal band resembles the convertase-resistant mutant of the zebrafish nodal homolog Southpaw, which exhibits a similarly short-range signal activity, rather than a complete loss of signal (Tessadori, et al 2015). The endogenous Hau-BMP5-8 may likewise be in a prodomain-bound form, regardless of whether it is proteolytically processed or not, and the presence of the prodomain may restrict the signaling range of BMP5-8, without interfering with its receptor binding.…”
Section: Proteolytic Processing By Proprotein Convertase Is Not Requicontrasting
confidence: 62%
“…Although we had not succeeded in verifying the cleavage of Hau-BMP5-8 in the germinal band, we nevertheless demonstrated that such cleavage is irrelevant to Hau-BMP5-8's ability to induce the P fate. This finding is in stark contrast to the situation in vertebrate embryos, in which overexpression of BMP4 or BMP7 with mutated cleavage sites has a dominant-negative effect (Hawley, et al 1995); on the other hand the apparent irrelevance of convertase-mediated cleavage in the leech germinal band resembles the convertase-resistant mutant of the zebrafish nodal homolog Southpaw, which exhibits a similarly short-range signal activity, rather than a complete loss of signal (Tessadori, et al 2015). The endogenous Hau-BMP5-8 may likewise be in a prodomain-bound form, regardless of whether it is proteolytically processed or not, and the presence of the prodomain may restrict the signaling range of BMP5-8, without interfering with its receptor binding.…”
Section: Proteolytic Processing By Proprotein Convertase Is Not Requicontrasting
confidence: 62%
“…The Nodal precursors are cleaved by extracellular convertases, and convertase processing was found to be essential for Nodal activation in zebrafish and mouse embryonic tissues ( Beck et al, 2002 ; Le Good et al, 2005 ). A recent report found that FurinA convertase activity regulates long range signaling by the zebrafish left-right patterning Nodal, Southpaw (Spaw), but not other Nodal factors ( Tessadori et al, 2015 ). Upon activation, Nodal proteins form complexes with type II and type I Activin receptors (Acvr1b; Acvr2a/b), which are serine/threonine kinases ( Reissmann et al, 2001 ; Yan et al, 2002 ; Yeo and Whitman, 2001 ) and activate the Nodal pathway ( Jia et al, 2008 ; Kumar, 2000 ; Massagué et al, 2005 ; Whitman, 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…Danio rerio (zebrafish) has become a favored model organism for studying biological processes due to their short period of reproduction, high reproduction rates, transparent embryos, and their ability to perform oviposition and fertilization in vitro (Bonora et al, 2015;Ding et al, 2015;Haesemeyer and Schier, 2015;Nishimura et al, 2015;Preston and Macklin, 2015;Wang et al, 2015). These unique properties make zebrafish particularly useful for studying embryogenesis, neurogenesis, hematopoiesis, organogenesis, and organ regeneration (Barriga et al, 2015;Navis and Bagnat, 2015;Panza et al, 2015;Tessadori et al, 2015).…”
Section: Introductionmentioning
confidence: 99%